Characterization of Extended-Spectrum β-Lactamase-Producing and AmpC β-Lactamase-Producing Enterobacterales Isolated from Companion Animals in Korea - Se Ra Shin; Seong Mi Noh; Woo Kyung Jung; Sook Shin; Young Kyung Park; Dong Chan Moon; Suk-Kyung Lim; Yong Ho Park; Kun Taek Park (MDPI AG, 2021)
The emergence of extended-spectrum cephalosporin (ESC)-resistant Gram-negative bacteria is of great concern in both human and veterinary medicine. The aim of this study was to investigate ESC-resistant bacterial isolates from companion animals in South Korea between 2017 and 2019. Isolates with ESC resistance genes, which were identified by PCR, were assessed for genetic relatedness by multi-locus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). In total, 91 ESC-resistant Escherichia coli, Klebsiella spp., Serratia spp., and Enterobacter cloacae isolates harbored the blaTEM gene. Among other ESC resistance genes, blaCTX-M-15, blaCIT, and blaCTX-M-55 were predominantly detected in E. coli isolates, whereas blaSHV and blaDHA were more frequently detected in Klebsiella pneumoniae isolates. In addition, all blaEBC-positive isolates were classified as E. cloacae. From the MLST results, blaCTX-M-9-carrying ST131, blaCIT-carrying ST405, and blaCTX-M-1-carrying ST3285 strains were dominant among E. coli isolates. ST273 and ST275 strains harboring blaSHV were frequently detected in K. pneumoniae isolates. Various sequence types were obtained in E. cloacae and Klebsiella oxytoca isolates. All isolates demonstrated unique PFGE profiles (<57-98% similarity) and were unlikely to be derived from a single clone. The present study reveals the presence and wide genetic distribution of ESC-resistant bacterial species in South Korean companion animals.